Pengembangan Desain Website Sebagai Media Promosi Produk Billboard Menggunakan Figma Dan Wordpress Pada Malangbillboard Di Kota Malang - M. Nurrahman Fanani; Heru Utomo (Jurnal Ekonomi dan Bisnis Digital, 2025)
Malangbillboard is a company focused on providing outdoor advertising media rental and installation services. The development was carried out by enhancing promotion through advertising media. Based on observations, the advertising media used by Malangbillboard are websites, Instagram, and word of mouth which are still not optimally managed. This study aims to develop a website design as a promotional medium using Figma and Wordpress. The research method used is action research involving 15 respondents consisting of 2 computer experts, 2 marketing experts, 1 company manager, and 10 potential consumers. The data collection methods used are observation, interviews, questionnaires, and documentation. Data analysis methods used are WebQual and EPIC Model to measure the quality and effectiveness of the website as a promotional medium. The results show that the website quality is very good, with a WebQual score of 0.87, and its effectiveness as a promotional medium is very effective, with an EPIC Model score of 3.63. From these results, it can be concluded that the developed website is very effective as a promotional medium for Malangbillboard.